APLIKASI ERGONOMI BERDASARKAN DATA ANTROPOMETRI PEKERJA PADA DESAIN ALAT KERJA - Ida Bagus Alit; I G.A.K. Chatur Adhi Wirya Aryadi; I Gede Bawa Susana (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Mataram, 2022)
A review of the application of ergonomics to design work tools based on worker anthropometric data is carried out to provide information on its use in the production process, especially in micro, small and medium business. This is done because most people in Indonesia still use simple tools with unnatural work postures. Unnatural work postures such as bending, squatting, twisting, exposure to the sun, etc. Unnatural work postures cause musculoskeletal complaints and fatigue which have an impact on decreasing work efficiency. Of course, this causes a decrease in productivity and quality of life for workers. From the results of a review of several studies and literature, satisfactory results were found regarding the application of ergonomics in designing work tools according to worker anthropometric data. Application of anthropometric data for the design or redesign of a work tool based on the flow of 1) determining the body that is important in the design or redesign, 2) determining the user population, 3) calculating the percentile value for each predetermined body dimension, and 4) application to the design of the tool. Ergonomics application based on information related to human factors (strengths, weaknesses, or limitations) in designing work tools that are more effective, safe, comfortable, healthy, and efficient. An ergonomic work tool can be used effectively, comfortably, safely, healthily, efficiently, and sustainably. Ergonomics application as an alternative in overcoming the problem of musculoskeletal complaints and fatigue due to unnatural work postures. Ergonomics applications improve work safety and worker health so that work productivity increases.